2016
DOI: 10.1083/jcb.201605093
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial division occurs concurrently with autophagosome formation but independently of Drp1 during mitophagy

Abstract: It remains controversial whether Dnm1/Drp1-mediated mitochondrial division is essential for mitophagy. Yamashita et al. show that Dnm1/Drp1-independent mitochondrial division occurs after formation of isolation membranes and in cooperation with autophagosome formation during mitophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
157
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 58 publications
13
157
0
2
Order By: Relevance
“…62 For instance, mitochondrial division during mitophagy can occur in a Drp1-independent manner. 63 On the other hand, Drp1-dependent mitochondrial fragmentation might facilitate mitophagy by creating small-size fragments facilitating autophagosomal uptake. 62 …”
Section: Discussionmentioning
confidence: 99%
“…62 For instance, mitochondrial division during mitophagy can occur in a Drp1-independent manner. 63 On the other hand, Drp1-dependent mitochondrial fragmentation might facilitate mitophagy by creating small-size fragments facilitating autophagosomal uptake. 62 …”
Section: Discussionmentioning
confidence: 99%
“…Molecular replacement strategies maintain the whole organelle by replacement of parts, perhaps analogous to the restoration of historic buildings. This third catchall category may involve the degradation and replacement of individual proteins, protein complexes or possibly the export of material destined for degradation through mitochondria-derived transport vesicles that pinch off from mitochondria independently of fission machinery or canonical autophagy machinery (McLelland et al, 2016; Soubannier et al, 2012; Sugiura et al, 2014), or by extraction directly from the tubular sides of mitochondria by attacking autophagosomes (Yamashita et al, 2016). Although several have estimated that at basal rates, cultured cells produce 50 autophagosomes per hour, it is currently not known what volume of mitochondrial biomass is turned over by any of these processes in neurons or other cell types, nor whether all of the different processes work in concert.…”
Section: Mitochondrial Turnovermentioning
confidence: 99%
“…However, more recent work identified a Drp1/Dnm1-independent mitophagy process conserved in yeast and mammals (Yamashita et al, 2016). In this case, distinct from organelle fission, small fragments of mitochondria are generated in the absence of Drp1/Dnm1 because they are apparently extracted from the sides of mitochondrial tubules by attacking autophagosomes (Yamashita et al, 2016).…”
Section: Mitochondrial Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests mDivi1 does not target Drp1 and instead functions as a mitochondrial complex I inhibitor . Additionally, there is mounting evidence for Drp1‐independent mitophagy . Remarkably, research from the Dorn laboratory revealed that mitophagy is actually promoted in the absence of Drp1 and inhibited in the absence of the fusion proteins Mfn1 and Mfn2 .…”
Section: Mechanistic Basics For Mitophagy Initiationmentioning
confidence: 99%